2018
DOI: 10.1002/etc.4036
|View full text |Cite
|
Sign up to set email alerts
|

Ractopamine in particulate matter emitted from beef cattle feedyards and playa wetlands in the Central Plains

Abstract: Beef cattle in the United States are routinely administered ractopamine, a β-adrenergic receptor agonist, to enhance growth. The present study is the first to quantify ractopamine in feedyard-emitted particulate matter and playa wetlands near feedyards. Ractopamine was present in 92% of particulate matter samples, 16% of playa sediment samples, and 3% of playa water samples, at maximum concentrations of 4.7 μg/g, 5.2 ng/g (dry wt), and 271 ng/L, respectively. These data suggest that aerial transmission and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…It is now well documented that PM generated on feed yards can contain antibiotics, β-agonists, endogenous and synthetic steroids, and pesticides (Blackwell et al, 2015;Longing et al, 2020;McEachran et al, 2015;Wooten et al, 2017). Pesticides and antibiotics are the predominant agrochemicals (per concentration basis) in PM emanating from beef cattle feed yards (Blackwell et al, 2015;McEachran et al, 2015;Peterson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well documented that PM generated on feed yards can contain antibiotics, β-agonists, endogenous and synthetic steroids, and pesticides (Blackwell et al, 2015;Longing et al, 2020;McEachran et al, 2015;Wooten et al, 2017). Pesticides and antibiotics are the predominant agrochemicals (per concentration basis) in PM emanating from beef cattle feed yards (Blackwell et al, 2015;McEachran et al, 2015;Peterson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These growth promotants may be transported via leakage from storage structures and run-off from feed yards and manure-amended soil [78,79] and in airborne particulate matter [80]. In the US, RC has been detected in airborne particulate matter (4700 ng/g) in the feed yard and also in water bodies (271 ng/L) near the feed yard [81]. The transport of RC in water bodies and the feed yard is possible, as a recent study by Challis et al [82] in Canada confirmed that by feeding RC to feedlot cattle for 42 days, RC was still detected in the pen floor feces during (13 days; 3600 ng/g) and post feeding (37 days; 681 ng/g) such that run-off manure from pen floors and pasture contained RC at concentrations of 6300 and 2100 ng/L, respectively.…”
Section: Environmental Contaminationmentioning
confidence: 99%
“…In North America, growth-promoting compounds including synthetic hormones, antibiotics, and β-adrenergic agonists are administered to beef cattle to improve health and increase feed efficiency . Manure generated from these feedlots not only contains beneficial nutrients and organic matter but also microorganisms, pharmaceuticals, and steroidal hormones that have the potential to adversely affect the health of wildlife or functions of the environment in general. Veterinary pharmaceuticals, including steroidal hormones trenbolone acetate, melengestrol acetate, , β-agonist ractopamine, , and associated metabolites, are commonly used to promote the growth of cattle in North American feedlots. A key challenge for feedlot managers and policymakers is to manage manure to optimize its economic value while minimizing environmental risks from associated veterinary pharmaceuticals …”
Section: Introductionmentioning
confidence: 99%
“…MGA is excreted primarily in feces and to a lesser extent in the urine . Ractopamine (RAC) is a β-adrenergic agonist used to promote feed efficiency and is administered as a feed additive for up to 42 days prior to slaughter. ,,, RAC is eliminated rapidly in cattle and swine, with 95% of the ingested amount (by mass) excreted within 3 days . While RAC is known to be eliminated in both urine (45%) and feces (55%), , quantitative measurements of metabolites in cattle have focused on urine, where the monoglucuronide conjugate comprises 95% of the compound mass excreted. , These growth-promoting compounds have been detected in feedlot manure, runoff, catch-basin water, and particulate matter, as well as surrounding surface waters and soils. , ,, However, concerns about their toxicity to aquatic nontarget organisms such as fish have mostly focused on TBA and metabolites 17α- and 17β-TBOH. Studies have observed altered sex ratios in zebra fish (Danio rerio) and fathead minnow (Pimephales promelas) skewed toward male fish as a result of near environmentally relevant exposures (10–25 ng L –1 ) to 17β-TBOH. , However, to the best of our knowledge, these effects have never been observed under practical production conditions in the field.…”
Section: Introductionmentioning
confidence: 99%